2012
DOI: 10.1111/jpm.12026
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary health professionals' assessments of risk: how are tools used to reach consensus about risk assessment and management?

Abstract: 'This is the peer reviewed version of the following article: GERACE, A., CURREN, D. and MUIR-COCHRANE, E. AbstractRisk assessment and management are among the most important and complex tasks health professionals undertake in their practice to prevent harm to patients and ensure safe and effective treatment. The aim of this study was to examine how multidisciplinary team members use tools to assess and manage risk, through examination of how tools are used to gather, record and "score" risk information; and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…, Gerace et al . ). Conversely, others proposed that they facilitate discussion between practitioners about risk and enhance care documentation (Muir‐Cochrane et al .…”
Section: Background Literaturementioning
confidence: 97%
See 1 more Smart Citation
“…, Gerace et al . ). Conversely, others proposed that they facilitate discussion between practitioners about risk and enhance care documentation (Muir‐Cochrane et al .…”
Section: Background Literaturementioning
confidence: 97%
“…In relation to risk assessment tools, only one study was located that reported nurses using validated tools or derivatives to guide their practice (Godin 2004); while some of the Community Mental Health Nurses (CMHNs) (n = 20) in this study reported using tools they still favoured clinical judgement and 'interpretative' approaches. Nurses in other studies, also report some ambivalence towards using tools, viewing them as a technology of psychiatry designed to erode clinical expertise or as bureaucratic instruments without value or purpose (Raven & Rix 1999, Murphy 2004, Muir-Cochrane et al 2011, Gerace et al 2013. Conversely, others proposed that they facilitate discussion between practitioners about risk and enhance care documentation (Muir-Cochrane et al 2011).…”
Section: Background Literaturementioning
confidence: 99%
“…Indeed, even when risk assessment measures are used in the clinical setting, absconding risk is often not included (Gerace et al . ). Reliable and valid data should drive any risk‐profile formulation and evidence‐based nursing interventions to reduce absconding (Fisher ; Mosel et al .…”
Section: Introductionmentioning
confidence: 97%
“…Although nurses regularly make informal assessments, 40 formal assessment of the risk of absconding is often not done in clinical practice. 41 No research has generated a reliable "absconder profile" or risk assessment tool for absconding. 42 Even the period that a patient has been an inpatient does not necessarily predict absconding risk.…”
Section: Prediction Of Abscondingmentioning
confidence: 99%